Unveiling SmearOFF Efficacy in Smear Layer Removal through Ultrasonic Activation Examined by Scanning Electron Microscopy - Hidayat Ababakr Khudhur; Diyar Khalid Bakr; Niaz Hamaghareeb Hamasaeed; Sazan Sherdl Saleem; Sohela Fakher Mahdi; Hozan Farid Tawfiq (International Journal of Biomaterials)
A layer of smear that coats the walls of root canals is produced by root canal instrumentation, which could be unfavorable to endodontic therapy. The endodontic irrigant SmearOFF is designed to effectively remove both the smear layer and bacteria concurrently. The objective of this study was to evaluate and compare the efficacy of SmearOFF and 17% EDTA in removing the smear layer across the coronal, middle, and apical thirds of root canals. Sixty-four single-canal mandibular premolar roots were chosen. Two irrigant protocols were separated into two sets of thirty-two teeth, respectively, Group 1 (6% NaOCL/SmearOFF) and Group 2 (6% NaOCl/17% EDTA.) Until X2, the ProtaperNext rotary system (Dentsply, Maillefer, Switzerland), with a COXO C-SMART Endomotor (Foshan COXO Medical instrument Co., Ltd., China) was utilized for the shaping of all teeth, the equipment settings were tuned to 300 revolutions per minute (rpm) and a torque of 3 Newton-centimeters (Ncm). Before applying the final irrigants, an initial irrigation with 6% sodium hypochlorite (NaOCl) was performed using a 27-G side-vented needle. An ultrasonic gadget, EndoUltra, was utilized to activate the irrigation. After that, the determination of how well the proposed solutions worked on the prepared teeth was conducted by scanning electron microscopy. The mean smear layer scores were lower in all three regions (coronal, middle, and apical) using 17% EDTA in comparison with the samples treated with SmearOFF. Despite that, there were no significant differences between G1, 6% NaOCL/SmearOFF and G2, 6% NaOCL/17% EDTA in smear layer removal according to Kruskal–Wallis tests and Mann–Whitney U-tests (p<0.05). Considering the findings of this investigation, both 17% EDTA and SmearOFF serve as chelating agents, demonstrating the capability to effectively remove the smear layer. This process is facilitated with the assistance of passive ultrasonic irrigation at intervals of every third of the root canal.